2015
DOI: 10.1037/adb0000018
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory cue reactivity in nicotine-dependent adult smokers.

Abstract: Cue-elicited reactivity is a significant factor in relapse during smoking quit attempts. Previous research has focused primarily on visual smoking cues, with very limited research examining reactivity to olfactory triggers. Twenty-six adult, non-treatment seeking, nicotine-dependent smokers were exposed to seven odorants during a cue-reactivity session measuring heart rate, skin conductance, and subjective craving. Cues included 2 cigarette odors (fresh tobacco and cigarette smoke), 2 odors previously identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
1
14
0
2
Order By: Relevance
“…Clusters were determined by Z > 2.3 with a corrected (cluster) significance threshold of p < 0.05 (Worsley, 2001). Previous data acquired in our laboratory revealed that while cigarette odors demonstrated significant effects in subjective and objective measures of cue-reactivity in nicotine-dependent adults, lavender and coffee odors were ineffective in this respect (Cortese et al, 2015). Given those findings, CIG-O was the focus of this preliminary investigation and therefore imaging data gathered during the other odor conditions (LAV-O and COF-O) were not assessed.…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Clusters were determined by Z > 2.3 with a corrected (cluster) significance threshold of p < 0.05 (Worsley, 2001). Previous data acquired in our laboratory revealed that while cigarette odors demonstrated significant effects in subjective and objective measures of cue-reactivity in nicotine-dependent adults, lavender and coffee odors were ineffective in this respect (Cortese et al, 2015). Given those findings, CIG-O was the focus of this preliminary investigation and therefore imaging data gathered during the other odor conditions (LAV-O and COF-O) were not assessed.…”
Section: Methodsmentioning
confidence: 88%
“…However, the decision to target the cigarette odor in the present analysis was justified, in part, by previous data acquired in our laboratory. We recently reported that cigarette odor, but not other odors including lavender and coffee, were effective elicitors of drug craving and associated physiological responses in nicotine-dependent individuals (Cortese et al, 2015). In the future, a full analysis including that of a neutral odor cue (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations